Pengaruh Citra Merek, Kualitas Produk, dan Promosi terhadap Keputusan Pembelian Laptop Acer - Aninditya Aji Nugraha; Handoyo Djoko W (Universitas Diponegoro, 2017)
With the increasing of human population and the growth of sains and technology causing the needing of product of technology becaming the primary needs, especially laptop. Many brands of laptop that available on the market, then there is increasingly intense effort from laptop company to capture large market share from other company. At this time segment of cars that become the market leader in Indonesia is Acer. However the sales of Acer Laptop in 2011-2014 are fluctuated. If it’s not addressed it will be a threat to it’s dominance on laptop market share.The purpose of this research was to determine the influences of brand image, product quality, and promotion, on purchase decision of Acer Laptop. This research method is explanatory on 100 respondents with purposive technique sampling. With data collection through interview, questioners, and literature review. The analysis technique used was quantitative. Quantitative analysis using cross tabulation, validity, reliability, correlation coefficient, coefficient of determination, simple and multiple regression analysis, as well as the significance test (t test and F test) and helped by application SPSS 16.0 for Windows.The result of statistic analysis known the influences of partially between brand image on purchase decision is 11,8 % product quality on purchase decision is 28,7 %, and promotion on purchase decision is 2,9 %,, the influences of simultaneously between product quality, promotion, and after sales service on purchase decision are 27,3 % whereas 72,7 % affected by other factors.From that results can be concluded brand image, product quality and, promotion influenced to purchase decision partially and simultaneously. Based on these conclusion so advice can be given for the Acer Company are to increasing brand image by increasing the quality of durability of laptop, notice the product quality with increasing the drurablity of laptop by replacing the hardware, doing exciting promotions and increase promotion frequency.